Seven brief lessons on physics - Rovelli, Carlo; Carnell, Simon & Segre, Erica (Trans) (Great Britain Penguin Random House, 2016)
In this mind-bending introduction to modern physics, Carlo Rovelli explains Einstein's theory of general relativity, quantum mechanics, black holes, the complex architecture of the universe, elementary particles, gravity, and the nature of the mind. Not since Richard Feynman's celebrated best-seller Six Easy Pieces has physics been so vividly, intelligently and delightfully revealed.
Keywords: Physics